2014
DOI: 10.1159/000363671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Renal Replacement Therapy on Renal Recovery after Acute Kidney Injury

Abstract: Recovery of kidney function following an episode of acute kidney injury (AKI) is now acknowledged as a vital patient-centered outcome with clear health economic implications. In approximately 5-8% of critically ill patients with more severe forms of AKI, support with renal replacement therapy (RRT) is provided. Recent data have suggested that rates of RRT utilization in AKI are increasing. Despite advances in our understanding of how best to prescribe acute RRT in critically ill patients with AKI, additional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…This may have been due to the high rate of shock after ROSC. These results are compatible with current standards because CRRT is recommended as the initial RRT modality [21]. A higher frequency of bleeding in the RRT group may have been caused by complications during the insertion of the dual-lumen haemodialysis catheter ( Table 1).…”
Section: Discussionsupporting
confidence: 85%
“…This may have been due to the high rate of shock after ROSC. These results are compatible with current standards because CRRT is recommended as the initial RRT modality [21]. A higher frequency of bleeding in the RRT group may have been caused by complications during the insertion of the dual-lumen haemodialysis catheter ( Table 1).…”
Section: Discussionsupporting
confidence: 85%
“…Another limitation of our study was that not all clinical details related to the AKI-D hospitalizations were available. We were missing information regarding etiology of preexisting CKD, indication for RRT initiation, initial RRT modality (e.g., intermittent vs. continuous therapy), physiologic variables at time of RRT initiation including APACHE score and urine output, inpatient medication use, and setting of AKI (e.g., sepsis or postsurgery); however, there is no definitive evidence that dialysis duration,12, 56 dialysis dose,57, 58 choice of dialysis membrane, 59 RRT modality,9, 12, 56, 59, 60, 61, 62, 63, 64 timing of dialysis initiation,65, 66, 67, 68 or medications such as diuretics69, 70, 71 are associated with chances of recovery. Although the specific etiology of AKI-D was also unavailable in our dataset, prior chart review of KPNC medical records by a board-certified nephrologist of similar cases showed that almost all were due to acute tubular necrosis 13, 15.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data have suggested that rates of RRT utilization in AKI are increasing ( 17 ). However, only 19% of all AKI patients included in our study were treated with RRT, which is similar with prevalence (12%) found in recent survey conducted in 10 Italian ICU ( 18 ).…”
Section: Discussionmentioning
confidence: 99%